On the effect of porosity and functional grading of 3D printable triply periodic minimal surface (TPMS) based architected lattices embedded with a phase change material. (February 2022) - Qureshi, Zahid Ahmed; Addin Burhan Al-Omari, Salah; Elnajjar, Emad; Al-Ketan, Oraib; Al-Rub, Rashid Abu
Highlights: Effect of Porosity and Topological grading on TPMS structures performance is presented. Both porosity and topological grading have significant impact on the TPMS structures' performance. A smaller porosity offers better heat transfer performance than a higher porosity but with a compromised PCM energy storage density. +ve grading in topology offers the best heat transfer performance regardless of the TPMS structure type and the mechanism of heat transfer. Abstract: Triply Periodic Minimal Surface (TPMS) topologies have recently gain widespread attention due to their promising performance in several areas like structural strength enhancement, heat transfer augmentation, scaffold and tissue engineering, etc. to name a few. Evolution in 3D printing technology has realized the manufacturing of these complex topologies in an extremely simplistic and straightforward manner. Recent research progress has shown that upon impregnations with phase change material (PCM), lattices based on TPMS topologies exhibited better heat transfer performance than the conventional metal foam in Latent Heat Thermal Energy Storage (LHTES) systems. However, the effect of lattice's porosity and functional grading is not understood and requires further investigation. In order to bridge this gap. This numerical study aims at studying the effect of porosity and functional grading of TPMS-PCM lattices on heat transfer performance. Three TPMS structures namely Primitive, Gyroid and IWP are considered in this study. The porosity study analyzes the heat transfer performance of TPMS structures at three distinct levels of porosity i.e., 60%, 75% and 90% with the 75% porosity case being the benchmark. Furthermore, to study the effect of functional grading, 75% uniform porosity configuration of each TPMS configuration was compared with 75% overall porosity configurations having first a positive and then a negative functional gradient in the porosity. It was found that both porosity and functional grading have a significant effect on both conductive and convective heat transfer enhancement. A reduction in porosity significantly reduces the PCM melting time owing to enhancement in the heat transfer. On the other hand, a positive gradient in the porosity outperforms both uniform porosity and negative porosity gradient cases. Moreover, in both porosity and functional grading studies, the extent of heat transfer enhancement is topology-dependent i.e., each TPMS structure exhibits a different extent of heat transfer enhancement that can be traced back to its topology. This study may therefore serve as a guideline for design and selection of a suitable TPMS candidate according to the applied boundary conditions/problem constraints of the respective LHTES system. Graphical abstract: Image, graphical abstract